2008
DOI: 10.5483/bmbrep.2008.41.10.705
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of NF-κB upon differentiation of mouse embryonic stem cells

Abstract: NF-κB is a transcriptional regulator involved in many biological

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 32 publications
(38 reference statements)
6
20
0
2
Order By: Relevance
“…Previously, we reported that expression and activity of NF-κB is comparatively low in undifferentiated human ES cells, but its expression increases during differentiation of ES cells when induced by retinoic acid (23). Recently, we also confirmed this phenomenon in mouse ES cells (24), which suggest that low NF-κB expression and activity is relevant in different species, and that NF-κB may contribute to differentiation rather than self-renewal of ES cells. Accordingly, TNF-α (23,24) and many other NF-κB agonists do not activate the NF-κB pathway in either human or mouse ES cells (our unpublished data).…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…Previously, we reported that expression and activity of NF-κB is comparatively low in undifferentiated human ES cells, but its expression increases during differentiation of ES cells when induced by retinoic acid (23). Recently, we also confirmed this phenomenon in mouse ES cells (24), which suggest that low NF-κB expression and activity is relevant in different species, and that NF-κB may contribute to differentiation rather than self-renewal of ES cells. Accordingly, TNF-α (23,24) and many other NF-κB agonists do not activate the NF-κB pathway in either human or mouse ES cells (our unpublished data).…”
Section: Introductionsupporting
confidence: 72%
“…Recently, we also confirmed this phenomenon in mouse ES cells (24), which suggest that low NF-κB expression and activity is relevant in different species, and that NF-κB may contribute to differentiation rather than self-renewal of ES cells. Accordingly, TNF-α (23,24) and many other NF-κB agonists do not activate the NF-κB pathway in either human or mouse ES cells (our unpublished data). A recent report by other investigators also suggested a differentiation inducing activity of NF-κB in mouse ES cells (25).…”
Section: Introductionsupporting
confidence: 69%
“…ESCs and early ES-derived vascular cells have been shown to have a low level of TNF-receptors, and it has been reported that nuclear factor-kB, a transcriptional regulator that plays a key role in immunity and inflammation, has relatively low expression in undifferentiated ES cells but increases during differentiation [68,69]. Expression of Toll-like receptors, a group of receptors associated with the immune and inflammatory response, have also been shown to be significantly downregulated in hESCs [70].…”
Section: Discussionmentioning
confidence: 99%
“…Mostrando que o modelo de indução de diferenciação em células pluripotentes pôde ser aplicado aos estudos seguintes que pretendiam entender melhor os mecanismos de sinalização de NFκB que estão envolvidos na manutenção da pluripotência bem como na diferenciação. Este resultado foi visto em outros trabalhos de indução de diferenciação mediada por atRA em células pluripotentes (COYLE; LI; BACCEI, 2011;KIM et al, 2008b;LU et al, 2009). A expressão do gene KLF4 (Figura 10C), em média, também se mostrou reduzida após os 4 dias de cultivo em presença de atRA, mas não foi significativa.…”
Section: Rt-qpcr Dos Marcadores De Pluripotênciaunclassified
“…Em outro trabalho posterior a este, o grupo mostrou que estes mesmos resultados eram vistos também em células-tronco embrionárias de origem murina (KIM et al, 2008b) …”
Section: Rt-qpcr Dos Genes Das Vias Canônica E Não Canônica De Nfκbunclassified